Learning Motivation and Self-Efficacy in English Among Seventh Graders - Tayag, Eunice S.; Tiamzon, Justine S.; Bagang, Ashley Nicole D.; Manalili, Jaymie Crizel N.; Frasco, Berna D.; Sarinas, Paulo; Buendia, Rose May; Dominado, Noel L. (Future Science / FSH-PH Publications, 2024)
The study aimed to evaluate learning motivation and self-efficacy among seventh graders. The result of the findings was the low of confidence in public speaking, business writing, and the lack of interest in English culture, history and literature. A mixed-methods sequential explanatory design was utilized, involving 283 seventh grade learners from one of the schools in Cluster 1 Division of Pampanga. The result of the study showed that the respondents have low confidence in writing an English letter, are afraid of public speaking, and lack interest in English cultural content. On the other hand, they see English as a tool for their future when they seek jobs or travel abroad, and they also see English as their motivation to study hard for their future career. Furthermore, the study also discovered connection between the two variables. Learning motivation could result from the positive outcomes of the students' insight when it comes to English; they would motivate themselves to master English. Although self-efficacy will determine their beliefs about their ability to learn, these learning motivations and self-efficacy further contribute to improving the learning confidence of a student. Finally, the findings have significance for boosting confidence and improving the abilities of the learners. Providing opportunities for students to use English in supportive environments, making English learning relevant and engaging, and helping students develop positive self-efficacy beliefs about their ability to learn English should be the main goals of interventions.